Safety, immunogenicity and protection of A(H3N2) live attenuated influenza vaccines containing wild-type nucleoprotein in a ferret model - Korenkov, Daniil A. (Infect Genet Evol, 2018)
Live attenuated influenza vaccines (LAIVs) are promising tools for the induction of broad protection from influenza due to their ability to stimulate cross-reactive T cells against influenza pathogens. One of the major targets for cytotoxic T-cell immunity is viral nucleoprotein (NP), which is relatively conserved among antigenically distant influenza viruses. Nevertheless, a diversity of epitope composition has been found in the NP protein of different lineages of influenza A viruses. The H2N2 master donor virus which is currently used as a backbone for the LAIV and donor of the six genomic segments encoding the internal proteins, A/Leningrad/134/ 17/57 (MDV Len/17), was isolated 60 years ago. As such, NP-specific T-cell immunity induced upon vaccination with classical LAIVs with a 6:2 genome composition containing this older NP might be suboptimal against currently circulating influenza viruses. In this study, a panel of H3N2 LAIV candidates with wild-type NP genes derived from circulating viruses were generated by reverse genetics (5:3 genome composition). These viruses displayed the cold adaptation and temperature sensitivity phenotypes of MDV Len/17 in vitro. LAIVs with both 6:2 and 5:3 genome compositions were attenuated and replicated to a similar extent in the upper respiratory tract of ferrets. LAIVs were immunogenic as high neutralizing and hemagglutination inhibition serum antibody titers were detected 21 days after infection. All vaccinated animals were protected against infection with heterologous H3N2 influenza A viruses. Thus, LAIV with a 5:3 genome composition is safe, immunogenic and can induce cross-protective immunity.